Analysis of vehicle braking dynamics with hydraulic braking system - Dahal, Chiranjivi; Labh , Sacheendra; Prakash Badu (Journal of Innovations in Engineering Education, 2023)
The stopping distance in vehicle is the distance require to safely stop after the driver has applied the brakes of vehicle. The stopping distance varies from road types to experience of driver. The objective of this study is to determine the stopping distance of vehicle for two different road condition: dry asphaltic and wet asphaltic. The methodology includes studying various factors involve in braking dynamics and validating the analytical calculation with Numerical methods. The velocity in which vehicle is travelling, coefficient of friction between road and vehicle tire plays important role in calculation of stopping distance. It was found that during wet season the stopping distance increased from 89 m to 99 m for vehicle travelling at 100 km/hr. The stopping time obtained from simulation in CarSim was 5.1 seconds for dry road and 6.4 seconds for wet road conditions.